Optimized molecular structures of guest–host system for highly efficient coatable polarizer. (October 2015) - Chang, Jae Bok; Namgoong, Jin Woong; Sakong, Chun; Choi, Jun; Park, Su Hyun; Hwang, Byoung Har; Kim, Jae Pil
Abstract: Various dichroic dyes were synthesized and applied to two different host materials for the study of optimized molecular structures of guest–host system for the coatable polarizer using liquid crystalline polymers. The host material containing planar and linear mesogens had an advantage in exhibiting high orientation orders, but easily formed disclinations due to causing the strong intermolecular attraction between the guest and host molecules. The balance of intermolecular attraction and repulsion between the guest and host molecules is important to simultaneously achieve high orientations and uniform alignments without disclinations. The highest dichroic ratio of coatable polarizers was obtained when the π-conjugation lengths of guest and host molecules have an appropriate ratio. Also, the guest molecules with a long π-conjugation length improved the orientation of host molecules. Graphical abstract: Highlights: Host-003 has a shorter and twisted (35.5°) mesogen compared to Host-006. Host-003 accommodated all synthesized dyes without disclinations. Host-006 easily formed disclinations with synthesized dyes. ST3 exhibited higher dichroic ratio in Host-006 than it did in Host-003.